BENTUK PERJANJIAN YANG DIBUAT ANTARA PEKERJA TOKO DAN PENGUSAHA PEMILIK TOKO DI DENPASAR - Prameswari, Citra; Mudana, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013, 2013)
In the article titled Form Agreement Made Between Workers andEmployers Store at Denpasar. The purpose of this paper is to understand the formof the agreement made between workers and employers stores at Denpasar.By using qualitative descriptive analysis method with random samplingtechnique (random sampling) results obtained in the field Form agreementsbetween employers and workers in the city of Denpasar shops are written or oralagreements or unwritten. Written agreement made mostly carried out on largestores while the agreement was not made in the form of a written or oralagreement which only form between workers and employers is usually done by theentrepreneur which stores they hold only a small shop.
Keywords: Forms of Agreement, Workers, Shop Owner